Epidemiological Survey of Frontotemporal Lobar Degeneration in Tottori Prefecture, Japan - Wada-Isoe, Kenji (S. Karger AG, 2012)
BACKGROUND: The prevalence of frontotemporal lobar degeneration (FTLD) in Japan is unknown. An epidemiological survey study of FTLD was undertaken in Tottori Prefecture, a district in the western region of Japan. METHODS: Hospitals in Tottori Prefecture were surveyed by a two-step questionnaire in 2010, and the prevalence of FTLD per 100,000 inhabitants was calculated using the actual number of patients and inhabitants in Tottori Prefecture on the prevalence day of October 1, 2010. RESULTS: In this survey, 66 patients were diagnosed with FTLD. The subtypes of FTLD were as follows: 62 cases of frontotemporal dementia (FTD), 3 cases of progressive nonfluent aphasia, and 1 case of semantic dementia. Among the FTD cases, 5 cases were FTD with motor neuron disease and 1 case was FTD with parkinsonism linked to chromosome 17. The prevalence of FTD in the total population of Tottori Prefecture was 11.2 per 100,000 inhabitants. Based on these results, the prevalence of FTLD in Japan in 2008 was estimated to be 9.5 per 100,000 individuals. CONCLUSIONS: Our epidemiological survey results suggest that there are at least 12,000 FTLD patients in Japan, indicating that FTLD is not a rare disease.